2014
DOI: 10.4040/jkan.2014.44.4.361
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Self-efficacy in the Relationship between Anger and Functional Health of Homeless Men

Abstract: Purpose: The purpose of this study was to examine the mediation of self-efficacy in the relationship between anger and the functional health of homeless men in order to provide a basis for planning nursing interventions to improve the functional health of homeless persons. Methods: The participants were 137 homeless men who lived in homeless shelters or visited one center serving free meals for homeless persons in Seoul. Data were collected using self-report questionnaires and analyzed with the SPSS-WIN 20.0 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
3
3
2
Order By: Relevance
“…Consistent with the findings of a study conducted by Cha & Sok (2014), nursing students exhibited a tendency towards controlling their anger effectively. However, the scores for anger-in and anger-out, considered as dysfunctional anger expression in our study, were higher relative to those observed in Korean homeless men with alcohol problems and difficulty in maintaining stable relationships in another study (Park & Kim 2014). Moreover, based on previous research indicating that dysfunctional anger expression patterns such as anger-in and anger-out, increased interpersonal problems in nurses and drinking problems in university students, nursing educators should be willing to support nursing students in dealing with their anger appropriately (Han et al 2015;.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…Consistent with the findings of a study conducted by Cha & Sok (2014), nursing students exhibited a tendency towards controlling their anger effectively. However, the scores for anger-in and anger-out, considered as dysfunctional anger expression in our study, were higher relative to those observed in Korean homeless men with alcohol problems and difficulty in maintaining stable relationships in another study (Park & Kim 2014). Moreover, based on previous research indicating that dysfunctional anger expression patterns such as anger-in and anger-out, increased interpersonal problems in nurses and drinking problems in university students, nursing educators should be willing to support nursing students in dealing with their anger appropriately (Han et al 2015;.…”
Section: Discussioncontrasting
confidence: 94%
“…This result supports the findings of previous studies, in which anger suppression increased internal anger, resulting in decreased self‐efficacy and difficulty in maintaining intimate relationships with others (Han et al. ; Park & Kim ; Park et al. ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Determination to seek housing is also arguably linked to how people perceive events that unfold in the world, and their ability to tackle adverse circumstances. However, only a handful of studies, focusing on personal outcomes, have looked closely at the role of efficacy and interventions for homeless people (Epel, Bandura, & Zimbardo, 1999;Park & Kim, 2014), which is surprising given that 'efficacy' is often viewed as synonymous with empowerment and/or wellbeing in the housing and homelessness literatures (see Clapham, Christian, & Foye, 2016). Within the domain of homelessness, Epel et al (1999) found, in a population of US homeless people, that those who had been previously employed and who had a higher level of educational achievement also had a more positive future orientation (a higher ability to plan for the future) despite current personal cir-cumstances.…”
Section: Efficacy and Psychosocial Factors Linked To Housing And Servicmentioning
confidence: 99%